2019
DOI: 10.1111/jicd.12462
|View full text |Cite
|
Sign up to set email alerts
|

Highly cited dental articles and their authors: An evaluation of publication and citation characteristics

Abstract: Aim In the present study, we aimed to identify and analyze the characteristics of highly cited articles in dentistry. Methods All articles belonging to Web of Science category of “dentistry, oral surgery and medicine” published until 2016 were analyzed. The bibliometric data of the highly cited articles were evaluated. The Y‐index was applied to assess authors’ publication potential. Altmetric scores were recorded from Dimensions, a free online database. Results There were 3666 highly cited dentistry articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…The characteristics of the analyzed set of HCPs are mostly in line with the verified features of the ESI highly cited articles in terms of a large number of authors and significant international cooperation [4,27]. More than half of analyzed HCPs (63.1%) were written by three or more authors, with an average number of authors per paper being 4.14, which is slightly higher compared to other studies exploring the most cited documents in dentistry [6].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The characteristics of the analyzed set of HCPs are mostly in line with the verified features of the ESI highly cited articles in terms of a large number of authors and significant international cooperation [4,27]. More than half of analyzed HCPs (63.1%) were written by three or more authors, with an average number of authors per paper being 4.14, which is slightly higher compared to other studies exploring the most cited documents in dentistry [6].…”
Section: Discussionsupporting
confidence: 66%
“…Bibliometric performance based on citation data has been widely analyzed in various fields of dentistry. Previously published bibliometric studies have described the most cited (also labeled as highly or top-cited) articles published in the field of Dentistry, Oral Surgery and Medicine [5,6] or in specific journal/s [7,8] or subareas, such as prosthodontics [9], pediatric dentistry [10], endodontics [11], orthodontics [12], dental implantology [13], periodontology [14], oral pathology and medicine [15], or oral and maxillofacial surgery [16]. However, in all these studies, the term highly cited paper refers to articles whose total number of received citations, mostly from the Web of Science (WoS) Core Collection, is equal to or higher than 100, regardless of the papers' publication date.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1,026 highly cited publications (0.95% of 107,437 documents in the category of emergency medicine in SCI-EXPANDED) with TC 2019 ≥ 100 were found including 898 highly cited articles (0.95% of 68,694 articles). It was reported that the percentage of highly cited documents was 0.68% in the category of health care sciences and services [6], and the percentage of highly cited articles in the category of dentistry, oral surgery and medicine was 1.8% [9]. To have scientific results, which can be repeated and checked, Ho's group proposed citation indicator TC year , the number of citations from Web of Science Core Collection since publication year to the end of the most recent year [11,12] and citations per publication (CPP year = TC year /TP) [14].…”
Section: Document Type and Language Of Publicationmentioning
confidence: 99%
“…The Y -index combines two parameters (j, h) to assess both the publication potential and the characteristics of the contribution as a single index. This indicator has also been applied to compare highly cited authors in Web of Science categories of health care sciences and services [6] and dentistry, oral surgery and medicine [9]. The Y -index is defined as [5,10]…”
Section: Countries Institutions and Authorsmentioning
confidence: 99%
See 1 more Smart Citation